Providers' utilization and perceptions of warfarin dosing algorithms - Gardner, Trevor; Vazquez, Sara R.; Kim, Kibum; Jones, Aubrey E.; Witt, Daniel M. (Thrombosis research, 2019)
Warfarin dosing algorithms have proven beneficial in increasing time within therapeutic range (TTR) and decreasing adverse events associated with out-of-range international normalized ratios (INRs). Despite widespread availability, providers' utilization and perceptions of warfarin algorithms in real-world practice are unclear. Identifying perceptions and barriers to algorithm use may help attempts to improve warfarin therapy management. Anticoagulation providers' utilization and perceptions of warfarin dosing algorithms were assessed via a nationwide electronic survey. Of the 246 providers who completed the survey, 82% were pharmacists, and 69% had over five years' experience dosing warfarin. Warfarin dosing algorithms were deemed beneficial by 84% of respondents and 72% currently use a warfarin dosing algorithm in their practice at least occasionally. Pharmacists were least likely of anticoagulation providers to use algorithms, although this was not statistically significant (p = 0.12). Algorithm utilization also decreased as years of warfarin dosing experience increased, with the highest rate of usage noted in the first year of dosing warfarin. The most common reason providers gave for discontinuing algorithm use was that they no longer felt it was needed. In this study, clinic patient volume did not appear to be associated with algorithm utilization. Warfarin dosing algorithms are frequently used among anticoagulation providers, especially those new to dosing warfarin, but use is frequently not sustained over the long-term. Education on the continued benefits of warfarin dosing algorithms could increase long-term utilization, potentially improving patient outcomes. •Most providers generally find warfarin dosing algorithms beneficial.•Three out of 4 providers use a warfarin dosing algorithm in their current practice.•Warfarin algorithm utilization declines as years of experience increases.•Warfarin dosing algorithms restricting clinical judgement is a barrier to use.